2020
DOI: 10.15258/sst.2020.48.3.09
|View full text |Cite
|
Sign up to set email alerts
|

Seed treatment with 5-azacytidine reduces ageing-induced damage in onion seeds

Abstract: The effect of treating aged onion seeds with 5-azacytidine (5-aza) on germination and vigour was evaluated. Seeds of two onion varieties, ‘Bhima Raj’ (BRJ) and ‘Bhima Red’ (BRD) were treated with 0, 10, 25 or 50 µg mL-1 5-azacytidine (a DNA demethylating agent). In comparison with the control treatment (0 µg mL-1 5-azacytidine), treatment with 5-azacytidine enhanced seed germination, seedling length, seedling dry weight and seed vigour indices. 5-azacytidine treatment also increased the act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…Seed ageing leads to accumulation of ROS, which damages the cellular membrane. The degraded membranes leach the solutes leading to loss of seed viability and vigour (Kurek et al, 2019;Yalamalle et al, 2020). In the present study, there was an increase in the EC with the seed age.…”
Section: Resultssupporting
confidence: 47%
“…Seed ageing leads to accumulation of ROS, which damages the cellular membrane. The degraded membranes leach the solutes leading to loss of seed viability and vigour (Kurek et al, 2019;Yalamalle et al, 2020). In the present study, there was an increase in the EC with the seed age.…”
Section: Resultssupporting
confidence: 47%
“…As a result, enzymes in the seeds are deactivated, and the germinability of the seed is gradually lost. Seed aging reduces the activities of enzymes associated with seed germination, such as SOD, CAT, and POD, thereby hindering germination [68]. The present experiment revealed that SOD, CAT, and POD activities decreased in aged wheat seeds.…”
Section: Discussionsupporting
confidence: 44%
“…Consequently, there is a huge need for new biochemical or molecular markers of seed viability that improve the process of monitoring plant material during storage in gene banks and to help with the understanding of the concomitant aging process occurring in seeds. These studies have developed rapidly over the last decade and substantiate the importance of volatile organic compounds [ 94 , 95 , 98 ], proteomic studies [ 191 ], RNA integrity [ 192 , 193 , 194 , 195 , 196 ] and DNA damage markers or epigenetic marks [ 96 , 97 , 99 , 190 , 197 , 198 , 199 , 200 ] that are highly promising and should be more widely explored.…”
Section: Discussionmentioning
confidence: 99%